Validation of the Antidiabetic and Hypolipidemic Effects of Clitocybe nuda by Assessment of Glucose Transporter 4 and Gluconeogenesis and AMPK Phosphorylation in Streptozotocin-Induced Mice. (3rd February 2014) - Shih, Chun-Ching; Chen, Mei-Hsing; Lin, Cheng-Hsiu
Abstract : The study was designed to investigate the effects of extract of Clitocybe nuda (CNE) on type 1 diabetes mellitus and dyslipidemia in streptozotocin- (STZ-) induced diabetic mice. Diabetes was induced by injection of STZ. Diabetic mice were randomly divided into five groups and given orally CNE (C1: 0.2, C2: 0.5, and C3: 1.0 g/kg body weight) or metformin (Metf) or vehicle for 4 weeks. STZ induction decreased in the levels of insulin, body weight, and the weight of skeletal muscle, whereas the levels of blood glucose, hemoglobin nonenzymatically (percent HbA1c), and circulating triglyceride ( P < 0.001, P < 0.001, and P < 0.01, resp.) were increased. CNE decreased the levels of blood glucose, HbA1c, and triglyceride levels, whereas it increased the levels of insulin and leptin compared with the vehicle-treated STZ group. STZ induction caused a decrease in the protein contents of skeletal muscular and hepatic phosphorylation of AMP-activated protein kinase (phospho-AMPK) and muscular glucose transporter 4 (GLUT4). Muscular phospho-AMPK contents were increased in C2-, C3-, and Metf-treated groups. CNE and Metf significantly increased the muscular proteins of GLUT4. Liver phospho-AMPK showed an increase in all CNE- and Metf-treated groups combined with the decreased hepatic glucose production by decreasing phosphenolpyruvate carboxykinase (PEPCK), glucose-6-phosphatase (G6Pase), and 11beta hydroxysteroid dehydroxygenase (11β -HSD1) gene, which contributed to attenuating diabetic state. The study indicated that the hypoglycemic properties of CNE were related to both the increased muscular glucose uptake and the reduction in hepatic gluconeogenesis. CNE exerts hypolipidemic effect by increasing gene expressions of peroxisome proliferator-activated receptor α (PPARα ) and decreasing expressions of fatty acid synthesis, including acyl-coenzyme A: diacylglycerol acyltransferase (DGAT) 2. Therefore, amelioration of diabetic and dyslipidemic state by CNE in STZ-induced diabetic mice occurred by regulation of GLUT4, PEPCK, DGAT2, and AMPK phosphorylation.